2016
DOI: 10.1186/s12916-016-0632-4
|View full text |Cite
|
Sign up to set email alerts
|

Modeling hormonal and inflammatory contributions to preterm and term labor using uterine temporal transcriptomics

Abstract: BackgroundPreterm birth is now recognized as the primary cause of infant mortality worldwide. Interplay between hormonal and inflammatory signaling in the uterus modulates the onset of contractions; however, the relative contribution of each remains unclear. In this study we aimed to characterize temporal transcriptome changes in the uterus preceding term labor and preterm labor (PTL) induced by progesterone withdrawal or inflammation in the mouse and compare these findings with human data.MethodsMyometrium wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
67
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(71 citation statements)
references
References 79 publications
3
67
0
1
Order By: Relevance
“…We collected the 101 abstracts and after analysing them, we found that most studies focused on preeclampsia, placental villi tissue, and animal models or maternal or cord blood. Six studies used RNAseq; two focused in cord blood [20,21], two on animal models [22,23] and two on the transcriptome of normal labor [12,24].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We collected the 101 abstracts and after analysing them, we found that most studies focused on preeclampsia, placental villi tissue, and animal models or maternal or cord blood. Six studies used RNAseq; two focused in cord blood [20,21], two on animal models [22,23] and two on the transcriptome of normal labor [12,24].…”
Section: Resultsmentioning
confidence: 99%
“…It has been proposed than pregnancy is maintained by down-regulation of chemokines at the maternal-fetal interface [25]. Removal of the down-regulation results in term birth while in the case of PTB, the activation of multiple pathways of the immune system overrides this down-regulation [3,22,25,2730]. In concordance with this idea, we found that up-regulated genes were mostly related to immune response (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Following bacterial administration, mice were placed in individual cages and continuously monitored with individual closed-circuit television cameras and a digital video recorder 68 . Time to delivery was recorded and defined as the number of hours from the time of bacterial administration to delivery of the first pup.…”
Section: Methodsmentioning
confidence: 99%
“…Following bacterial administration, mice were placed in individual cages and continuously monitored with individual closed-circuit television cameras and a digital video recorder (29). Time to delivery was recorded and defined as the number of hours from the time of bacterial administration to delivery of the first pup.…”
Section: Ascending Vaginal Infection Modelmentioning
confidence: 99%